Annual Report of Congressional Research Service of the Library of Congress for Fiscal Year 2015 (Congressional Research Service (CRS), 2016)
Báo cáo thường niên về dịch vụ nghiên cứu Quốc hội của Thư viện Quốc hội năm tài chính 2015 của Hoa Kỳ